0.5% CARBOXYMETHYLCELLULOSE VERSUS 0.4%POLYETHYLENE GLYCOL / 0.3% PROPYLENE GLYCOL AS TEAR SUBSTITUTES FOR THE TREATMENT OF DRY EYE - Dr Shweta Sinha ,Dr Ritu Jain (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Dry eye disease (DED) is a multifactorial disorder characterized by tear filminstability, ocular surface inflammation, and discomfort, leading to impaired vision and qualityof life. Artificial tear substitutes are the cornerstone of management, with Carboxymethylcellulose (CMC) and Polyethylene Glycol/Propylene Glycol (PEG/PG) beingwidely used. Objective: To compare the efficacy of 0.5% CMC and 0.4% PEG/0.3% PG eye drops in patientswith mild to moderate DED.